129k views
3 votes
Using the functions f(x) = 5x - 12 and g(x) = 11x + 2 to complete the function operations listed below.

Part A: Find (f + g)(x). Show your work

Part B: Find (f × g)(x). Show your work

Part C: Find f[g(x)]. Show your work

User Spinkus
by
5.7k points

1 Answer

5 votes

A) (f + g)(x) = f(x) + g(x) = (5x-12) + (11x+2) = 16x-10

B) (f × g)(x) = f(x)×g(x) = (5x-12)×(11x+2) = 5x(11x) -12(11x)+2(5x) -12(2) = 55x² -122x -24

C) f(g(x)) = 5(11x+2) -12 . . . . substitute g(x) for the x in f(x)

... = 55x +10 -12 = 55x -2

User Manita
by
5.9k points